Ziguezon’s Voyage: Modal Memory and Cultural Transformation from France to Quebec - Poliquin, Laurent (SPC Journal of Social Sciences, 2025)
This article explores how oral traditions preserve memory, subvert authority, and reinvent identity by tracing the transatlantic journey of “La Ziguezon”, a French folk song that La Bottine Souriante revived in Quebec in 1983. Drawing on historical chansonniers, ethnomusicological studies, and oral recordings, it examines how the song evolved from a 16th-century Breton ballad into a contemporary emblem of Québécois folklore. Focus is given to its melodic resilience, nonsense refrain (“ziguezon zinzon”), and gendered narrative, in which a young woman rejects patriarchal reward and composes her own response. Methodologically, the study blends textual comparison, musical analysis, and critical folklore theory to examine “La Ziguezon” as both artifact and performance. A comparative table highlights its adaptability across regions, eras, and singers. The article also reflects on the challenges of studying oral material within a print-based aca-demic paradigm. Findings suggest that the song endures not through fixed meaning but through its rhythmic structure, performative irony, and mnemonic potency. Its absurd refrain functions as a ritual of resistance, enabling marginal voices—especially female ones—to reclaim agency through rhythm and play. Rather than preserving the past, “La Ziguezon” embodies what this study calls an “improvised archive”: a living, rhythmic form that adapts across generations. Ultimately, the article argues that folk songs like “La Ziguezon” are not cultural fossils but dynamic sites of memory and subversion—traditions that survive precisely because they can be sung anew.